Nb-doping of TiO2/SrTiO3 nanotubular heterostructures for enhanced photocatalytic water splitting - Yang, Yang; Lee, Kiyoung; Kado, Yuya; Schmuki, Patrik (Electrochemistry Communications, 2012)
Ti alloys with low Nb contents (0.1 at.% and 0.5 at.%) were used to grow self-organized Nb-doped TiO2 nanotube arrays. These layers were partially converted to SrTiO3 using a hydrothermal treatment. Various factors, such as hydrothermal temperature, hydrothermal duration, and annealing conditions, were investigated in view of the photocatalytic water splitting performance of the formed Nb-doped TiO2/SrTiO3 heterostructure nanotubes. Photoelectrochemical characterization shows that Nb-doping efficiently enhances the photocatalytic water splitting performance of TiO2/SrTiO3 heterostructure nanotubes.
EAM Import::2019-03-12